High brilliant thermal and cold moderator for the HBS neutron source project Jülich. (September 2016) - Cronert, T; Dabruck, J P; Doege, P E; Bessler, Y; Klaus, M; Hofmann, M; Zakalek, P; Rücker, U; Lange, C; Butzek, M; Hansen, W; Nabbi, R; et al.
Abstract: The proposed High Brilliance Neutron Source (HBS), recognized within the Helmholtz Association of German Research Centres, will optimize the entire chain from particle source through particle accelerator, target, moderator, reflector, shielding, beam extraction, beam transport all the way to the detector, utilizing the nuclear Be(p, n) or Be(d, n) reaction in the lower MeV energy range. A D2 O moderating reflector prototype (MRP) and a cold source were constructed and build according to MCNP parameter studies. The MRP was tested in a feasibility study at the TREFF instrument at MLZ (Garching). Cold beam extraction from the flux maximum within the moderator based on liquid para H2 and other cold moderators will be tested by energy spectroscopy via TOF-method. Different ratios of liquid ortho/para H2 will be fed to the cold moderator. The ratio will be controlled by feeding from reservoires of natural liquid H2 and a storage loop with an ortho/para converter and determined via online heat capacity measurement.